Population genetics of South African Protea L. (Proteaceae) species associated with various pollinator guilds - Smith, Megan (Department of Biological Sciences, 2020)
South Africa hosts plant species with a large variety of floral traits associated with different pollinator guilds. Suites of specialised floral traits associated with particular pollinators are known as pollination systems or syndromes. However, it is often uncertain how these pollination systems affect gene flow between plant populations, mating system outcome, and subsequent genetic health of plant species. Genetic variability is an important aspect in understanding the long-term survival of a species because excessive homozygosity, as a result of high amounts of inbreeding, may restrict a species’ long-term local adaptive potential. The African genus, Protea, is an ideal study system for exploring the evolution and maintenance of mating systems, because the pollination system for many species have been confirmed by pollinator exclusion experiments. The genus has several pollination systems including birds, insects and non-flying mammals. Comparative estimates of pollinators’ outcrossing abilities are rare and confined to bird and insect guilds. Furthermore, 10 microsatellite markers have been developed for the genus, but have not been used to assess the outcrossing abilities of various pollinators. This study thus had two aims: Firstly, to use microsattelite markers to estimate the outcrossing rates and subsequent genetic diversity of Protea species primarily pollinated by either birds (P. laurifolia and P. roupelliae), insects (P. caffra and P. simplex) or non-flying mammals (P. amplexicaulis and P. humiflora). Secondly, I aimed to understand how birds and non-flying mammal pollinators affect population connectivity and gene dispersal. This was done by comparing indirect estimates of gene flow in the therophilous, P. amplexicaulis, and ornithophilous, P. laurifolia. These estimates included population differentiation (G”st) between subpopulations and spatial genetic structuring within metapopulations of each species. I expected that less vagile pollinators, such NMP’s (non-flying mammal pollinators), would contribute the least to gene flow and cause high selfing rates and low genetic diversity within therophilous populations. Contrastingly, flying pollinators would be able to travel longer distances resulting in more genetic connectivity between plant populations. The high energetic demands and interplant movements of flying animals were predicted to result in high outcrossing rates in ornithophilous and entomophilous species. Non-flying mammal-pollinated (NMP) Protea species had high (> 0.8) and non-significantly different (p > 0.05) outcrossing rates relative to species pollinated by flying animals. Similarly, hand pollen supplementation experiments also revealed that small mammals were effective pollen vectors since P. amplexicualis individuals were not pollen limited. High multilocus outcrossing rates (> 0.80) may have resulted in all sampled Protea species exhibiting high levels of heterozygosity (> 0.7) and low levels of inbreeding. However, some of the outcrossing events were between kin (approximately 14 %), giving evidence for biparental inbreeding. Furthermore, the relationship between geographic distance and genetic distance was significant for sampled P. amplexicaulis individuals. In contrast, sampled P. laurifolia individuals were genetically similar across the landscape. This pattern was reflected in fine-scale (> 500 m) spatial genetic structuring in a sampled metapopulaton of P. amplexicaulis and a homogeneous distribution of P. laurifolia genotypes. Restricted gene dispersal recorded for P. amplexicaulis in this study may have been a result of the high levels of biparental inbreeding. It was not clear whether poor gene flow was primarily a result of restricted pollen dispersal created by NMP’s or restricted seed dispersal. Nevertheless, continuous limited gene dispersal between NMP populations may result in allopatric speciation over time. This provides a hypothesized reason as to why many of the therophilous Protea species are located in small and isolated populations. Additionally, there is a concern that restricted population size in combination with poor gene flow may lead to increased levels of inbreeding over time. This study provided the first evidence for localised gene dispersal, but high outcrossing rates, in NMP proteas.